1990
DOI: 10.1099/00222615-31-2-119
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Pseudomonas aeruginosa in patients with cystic fibrosis

Abstract: Summary. The occurrence of various Pseudomonas aeruginosa strains in the sputum of 15 patients with cystic fibrosis (CF) was monitored over periods ranging from 2 to 60 months. Isolates of P . aeruginosa were typed by four different techniques, namely serotyping, active and passive pyocin typing, and phage typing. The maximum number of different serotypes found in the patients was three (one serotype in nine patients; two serotypes in five patients; three serotypes in one patient). Pyocin and phage typing show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
2
9
0
3
Order By: Relevance
“…Also, in patients with respiratory tract infections due to P. aeruginosa, in spite of intensive treatment with ciprofloxacin bacterial persistence has been described by various authors (1,7,12,16,31). Successful eradication of bacteria from lung tissue chronically infected with P. aeruginosa is probably hampered by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in patients with respiratory tract infections due to P. aeruginosa, in spite of intensive treatment with ciprofloxacin bacterial persistence has been described by various authors (1,7,12,16,31). Successful eradication of bacteria from lung tissue chronically infected with P. aeruginosa is probably hampered by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…The initially acquired strain persisted over the whole study period; only two patients lost their clone after 3 years. Horrevorts et al [3] monitored 15 CF patients over periods up to 5 years, applying serotyping, phage typing, and pyocin typing. They found that, generally, one serotype predominated and that the colonization with P. aeruginosa was quite constant.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, again, antibiotic resistance mechanisms evolved coincidentally with the introduction of new antibiotic derivatives, compromising the most effective treatments (such as the ␤-lactams and aminoglycosides). P. aeruginosa is of considerable concern for patients with cystic fibrosis (76); the pathogen is highly persistent and can avoid human immune defenses. Resistance development is associated with the lengthy antibiotic treatment of cystic fibrosis patients.…”
Section: Superbugs and Superresistancementioning
confidence: 99%